Land suitability for growing tilapia (Oreochromis niloticus) with biofloc technology in the state of Durango, México - Garza-Martínez, Miguel Ángel; Alonzo-Rojo, Fernando; Valenzuela-García, Ana Alejandra; Nava-Camberos, Urbano; Salcido-Gameros, David; Estrada-Arellano, Josué Raymundo; Cardoza-Martínez, Gabriel Fernando (Ecosistemas y Recursos Agropecuarios, 2021)
Durango state has ideal territorial, climatic and hydrological conditions to increase aquaculture development; however, in recent years the production of this activity has decreased and descended to the last places at the national level. One of the alternatives for a sustainable aquaculture development in the state is the application of Biofloc Technology (BFT) in production units of tilapia. The aim of this study was to determine the land suitability of the state for tilapia production with BFT, as well as to analyze the aptitude in marginalized municipalities of the state according to the Human Development Index (HDI). A Multi-criteria evaluation was carried out by means of weighted sum with the support of a group of experts. An aptitude map for the activity was generated through Geographic Information System. Five categories of aptitude were established: Very Low, Low, Medium, High and Very High. An area with High and Very High aptitude of 50 182 km2 was estimated to develop the activity in the state. The regions with the highest aptitude were found in the central east and north of the state, mainly in the semi-arid zone. 39.67 % of the High and Very High aptitude estimated for the activity was concentrated in the municipalities with a Medium or Low HDI, which represents an opportunity to increase food security in these municipalities. The results of this study will allow increasing the certainty in the implementation of aquaculture projects in the state with a focus on optimal use of resources.